Implementation of Transformational Management on Lecturer Performance and Motivation at the Indonesian Institute of Business and Computers - Raja, Edward A. Lbn.; Rosli, Rozaini Binti; Sitanggang, Eva Rianty (CV. Rayyan Dwi Bharata, 2023)
The implementation of transformational management on the performance and motivation of lecturers at the Indonesian Institute of Business and Computers really needs to be done by a leader in an institution or organization. Research on the implementation of transformational management on the performance and motivation of lecturers at the Indonesian Institute of Business and Computers has been carried out. This research is an empirical study at the Indonesian Institute of Business and Computers. The purpose of this research is to see the implementation of transformational management on the performance and motivation of lecturers at the Indonesian Institute of Business and Computers. From the research results, the role of transformational management becomes very important in the success of an organization for the performance of its subordinates. This research is a descriptive study with a sample of 62 permanent lecturers regarding the performance and motivation of lecturers at the Indonesian Institute of Business and Computers. The technique used in carrying out this research was distributing questionnaires to all respondents to be filled out and collected. From the results of the tabulation of research data on the indicators of lecturer motivation, it was obtained by 85.00% and for the performance indicators, it was obtained by 86.67%. From the results of the study it was concluded that the implementation of transformational management on the performance and motivation of lecturers at the Indonesian Institute of Business and Computers was very good.